Kesan terhadap peserta yang mengikuti projek ICT di luar bandar - Abu Hassan, Musa; Ismail, Narimah; Omar, Siti Zobidah; Bolong, Jusang (Universiti Putra Malaysia Press, 2008)
The purpose of this paper is to examine the effect of rural ICT projects established and managed by various government and non-government organizations on the knowledge and skills of project participants. Data were collected through personal interview involving 1250 respondents from all states in Malaysia. Generally, the respondents admitted that they had gained computer knowledge and skills after participating in the programs organized by the rural ICT project centre. It was found that 77.1% of the respondents said that they now know how to use computer after going through the program in their locality. Likewise, almost two third of the respondents said that they now know how to use the internet after going through the program organized by the rural ICT project centre. The results also showed that most respondents had an increase on knowledge concerning hardware, software and selected application. Thus, rural ICT project centres need to be further strengthened in providing services because the respondents stated that the centres had brought positive impact with regard to computer knowledge and skills.